Mengungkap kekuatan retorika dalam pidato Presiden Prabowo Subianto “Singgung Tarif Trump” (Analisis wacana kritis Fairclough) - Tri Indrayanti; Ani Rakhmawati; Kundharu Saddhono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
In the contemporary political landscape, state speeches are crucial areas for the manifestation of power and the formation of public opinion. This study aims to investigate how President Prabowo Subianto utilizes speech strategies in his speech alluding to the “Trump Tariff” and explores how political speeches are used to strengthen the legitimacy of power, build national identity, and manage power relations in the Indonesian socio-political context. The focus of the study is on identifying rhetorical elements that are strategically used to shape perceptions. The approach used in the critical approach is Fairclough’s Critical Discourse Analysis with a descriptive qualitative method. The analysis carried out includes various discursive elements such as legitimacy strategies, strengthening hegemony, forming collective identities, and the influence of discourse on the audience. The results of the study show that President Prabowo Subianto’s speech fulfills three elements of Fairclough’s dimensions. In addition to the three elements of Fairclough’s dimensions, researchers found uniqueness in President Prabowo’s speech, namely the strategy of using polarity, the use of discursive strategies, intertextuality and interdiscursivity, hegemony strategies and re-narratives of power, the construction of collective and national identities, discursive strategies in speeches, and the use of high-level narratives of legitimacy of power.